Experimental validation of integrated steering and braking model predictive control. (17th May 2010) - Falcone, P.; Borrelli, F.; Tseng, H.E.; Asgari, J.; , D. Hrovat
We present and discuss an in-vehicle experimental validation of an integrated steering and braking Model Predictive Control (MPC) algorithm. The experimental results are obtained in autonomous path following tests, where the vehicle autonomously performs a double-lane change manoeuvre by simultaneously coordinating the front steering and the braking torques at the four wheels. The manoeuvres are performed at high speed on slippery surfaces to operate close to the vehicle stability limits. Experimental tests of double-lane change manoeuvres at 70 kph are shown and complex countersteering manoeuvres are presented and discussed.